Factors that influence flow through intravascular catheters: the clinical relevance of Poiseuille's law. Issue 7 (8th July 2020) - Berman, David J.; Schiavi, Adam; Frank, Steven M.; Duarte, Shirley; Schwengel, Deborah A.; Miller, Christina R.
Abstract : BACKGROUND: The physics of ideal fluid flow is well characterized. However, the effect of catheter size, tubing types, injection port adjuncts, and viscosity on flow is not well described. We used a simulated environment to determine how various permutations of common elements affect fluid flow. STUDY DESIGN AND METHODS: We tested 16 peripheral and central venous catheters to assess flow through several standard infusion sets and a rapid infuser set; tested flow through standard and blood infusion sets with the addition of intravenous extension tubing, stopcocks, and a needleless connector; and compared the relative viscosity of commonly used blood products and colloids to that of normal saline. RESULTS: The maximal flow rate was 200 mL/min for the standard infusion set but 800 mL/min for the rapid infusion set. Choice of infusion tubing was the rate‐limiting component for many larger catheters. A 14‐gauge, single‐lumen central venous catheter (CVC) and 18‐gauge peripheral intravenous catheter (PIV) had equivalent flow rates with all infusion sets. A 16‐gauge single‐lumen CVC allowed a flow rate that was slower than that of a 20‐gauge PIV, and faster than that of a 22‐gauge PIV. The addition of adjuncts slowed flow rate. Needleless connectors had the greatest impact, reducing flow by 75% for the blood infusion set. Packed red blood cells had a viscosity 4.5 times that of normal saline and thereby reduced flow. CONCLUSION: Catheter and tubing choice, adjuncts, and fluid viscosity influence flow rates. Our results will help inform adequate vascular access planning in the perioperative environment.